PENGARUH PEMBERIAN DAUN SELEDRI PADA LANSIA PENDERITA HIPERTENSI TERHADAP PENURUNAN TEKANAN DARAH DI DESA SRINGIN KECAMATAN JUMANTONO - Herminto, Budi; Aminingsih, Sri; Mugiarsih, Sriyani (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2013)
Background. Some study showed that celery of many substances such asglukoside apiin, isokuersetin, umbiliseron, calsium, triptofan and also somevitamins. The substance have pharmalogical effect, one of them is reducing theblood pressure.The purpose Of this study was to determine the effect of consuming celery toreduction of high blood pressure in elderly who suffered hypertension.The subject Used in this study were the elderly who suffered hypertensionSringin village. The sampling technique used total sampling and the total numberof sampling were 35 people.Methods Used in this study was pre experiment design. 10 peoples consumingcelery once a day, 10 peoples consuming celery twice a day and 15 peoplesconsuming celery more than three times a day. All the people was suggested toconsuming celery during one month. The blood pressure was measured twotimes, before and after consuming celery. Data processing used paired t-teststatistical test with significan level Î± = 0,05.Conclusion The result showed p = 0,0001. It can be concluded that consumingcelery gave significant effect on reducing blood pressure in elderly withhypertension.Keywords: reduction in high blood pressure,celery